ПІДХІД ДО АКТИВНОГО ЕКРАНУВАННЯ МАГНІТНОГО ПОЛЯ ЛІНІЇ ЕЛЕКТРОПЕРЕДАЧІ НА ОСНОВІ АЛЬФА-БЕТА ПЕРЕТВОРЕННЯ ЇЇ СТРУМІВ - Грінченко, В.С. (Інститут електродинаміки НАН України, Київ, 2014)
This paper deals with the active shielding of the magnetic field of a flat three-phase power line. The present study considers active loops with the magnetic moment opposite to the magnetic moment of the β-component currents circuit, arising in alpha-beta transformation applied to three-phase power line currents. Relationship between the size of the proposed active loops and the electric current is derived. Presented results show that such active loops allow reduction of the width of sanitary-hygienic zone under power lines, where the magnetic flux density exceeds the reference level, by 11% compared to the known active loops. References 5, table 1, figures 3.